2013
DOI: 10.1534/genetics.113.156299
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Targeted Mutagenesis in Caenorhabditis elegans

Abstract: The generation of genetic mutants in Caenorhabditis elegans has long relied on the selection of mutations in large-scale screens. Directed mutagenesis of specific loci in the genome would greatly speed up analysis of gene function. Here, we adapt the CRISPR/Cas9 system to generate mutations at specific sites in the C. elegans genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
135
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 19 publications
(27 reference statements)
4
135
2
5
Order By: Relevance
“…Our efforts at Cas9-directed editing succeeded with all 39 GG guides. In contrast, success was infrequent and unpredictable with guides lacking a 39 GG in our study and in published studies (Table S1) We also found that a 39 GG dinucleotide reliably increased the frequency of genome editing at all targets, even related targets for which the 39 GG-shift guides supported a low to modest frequency of editing.The median frequency of NHEJ-mediated mutagenesis for successfully edited C. elegans targets was 4.3% (range of 0.2-100%) in published studies using DNA sequence to screen targets in transgenic F 1 animals expressing Cas9 (Table S1) Waaijers et al 2013;Kim et al 2014). In contrast, the median frequency of editing for targets in our study was 51% (range of 10-72%) (Table S1), a 10-fold increase (P # 0.02.…”
contrasting
confidence: 58%
See 3 more Smart Citations
“…Our efforts at Cas9-directed editing succeeded with all 39 GG guides. In contrast, success was infrequent and unpredictable with guides lacking a 39 GG in our study and in published studies (Table S1) We also found that a 39 GG dinucleotide reliably increased the frequency of genome editing at all targets, even related targets for which the 39 GG-shift guides supported a low to modest frequency of editing.The median frequency of NHEJ-mediated mutagenesis for successfully edited C. elegans targets was 4.3% (range of 0.2-100%) in published studies using DNA sequence to screen targets in transgenic F 1 animals expressing Cas9 (Table S1) Waaijers et al 2013;Kim et al 2014). In contrast, the median frequency of editing for targets in our study was 51% (range of 10-72%) (Table S1), a 10-fold increase (P # 0.02.…”
contrasting
confidence: 58%
“…All guides designed for all targets supported robust genome editing, both imprecise NHEJ events and precise, templated HDR events. The median frequency of editing at all targets was 51% without any coselectable markers, a 10-fold increase above previous studies that also reported numerous guide RNAs in the nonfunctional class Waaijers et al 2013;Kim et al 2014). Combining our already effective guide RNA design with the co-conversion/ co-CRISPR strategy of others (Arribere et al 2014;Kim et al 2014;Ward 2014) enhanced the ease of mutant recovery and boosted our median for both precise and imprecise genome editing to 86%.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…Compared with the zinc finger nucleases (ZFN) and transcription activator-like effector nucleases (TALEN), which have been used for genome editing [1], the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/ CRISPR-associated (Cas) system has emerged as a new powerful tool for genome modifications. It has recently been adopted for genome editing in human cell lines [2][3][4], mouse [5], zebrafish [6], C. elegans [7][8][9][10][11][12], and plants [13].…”
mentioning
confidence: 99%